Pengaruh Return On Asset (ROA), Return On Equity (ROE) Dan Earning Per Share (EPS)Terhadap Harga Saham Pada Perusahaan Sub Sektor Makanan Dan Minuman Di Bursa Efek Indonesia Tahun 2014-2018 - Sasi Sabrina; Dinalestari Purbawati (Universitas Diponegoro, 2020)
Stock price is the money incurred to obtain proof of inclusion or ownership of a company. The stock price has changed up or down over time. It is caused by various factors, both internal and ext ernal factors. In the last five years, ROA, ROE and EPS are companies sub-sector of food and beverage tends to experience a decline. While the stock price of companies sub-sector food and beverage tends to increase. The research aims to test the influence of ROA, ROE and EPS on the price of shares in food and beverage sub-sector companies. This type of research is an expreslanative, with a population that can be examined in the sub -sector of food and beverage as many as 14 companies. The data source type is the secondary data obtained indirectly. The data types used in this study are time series and cross section data. The data analysis methods used are the classic assumption test, correlation test, coefficient of determination test, regression test and signi ficance test by using SPSS 21 application. The results of this study stated that the influence of ROA, ROE and EPS was a positive and significant influence on the stock price of 40.6%, while the remainder of 59.4% was described by other variables not inclu ded in the model. Based on this and the limitations in this research, researchers have some advice for companies to maintain the stability of profit and financial performance of the company. And for investors who will invest in the company, in addition to seeing the company's financial performance, it is also worth considering other factors beyond the control of the company (external factors)